Probabilistic scenarios for assessing setup uncertainty in VMAT and IMPT plans for lung cancer - Teoh, S; Fiorini, F; George, B; Vallis, K; Van Den Heuvel, F (Elsevier, 2018)
Purpose or Objective: To evaluate and compare robustness of intensity modulated proton therapy (IMPT) and volumetric modulated arc therapy (VMAT) for stage III non-small cell lung cancer (NSCLC) for setup uncertainties using probabilistic scenarios.